Detecting hydrogen using TiO2-B2O3 at different operating temperature - Mohd Chachuli, Siti Amaniah; Hamidon, Mohd Nizar; Mamat @ Mat Nazir, Md Shuhazlly; Ertugrul, Mehmet (IEEE, 2018)
Performance of TiO2-B2O3 gas sensor that annealed using nitrogen at 650°C for 30 minutes was observed and analyzed. The sensing film of the gas sensor was prepared by mixing TiO2-B2O3 with an organic binder. The sensing film was characterized by field emission scanning electron microscopy (FESEM) and X-ray diffraction (XRD). The gas sensor was exposed to hydrogen at a concentration of 100-1000 ppm with operating temperatures of 100°C and 200°C. However, no response was detected for 100 ppm at 100°C. But, as the operating temperature was increased to 200°C, the gas sensor indicated a good response for 100 ppm of hydrogen. The gas sensor exhibited p-type response based on decreased current when exposed to hydrogen. The sensitivity of gas sensor was calculated at 1.00, 2.18 and 3.58 for 100 ppm, 500 ppm and 1000 ppm respectively, at an operating temperature of 200°C.